Positive Interaction between H2O2 and Ca2+ Mediates Melatonin-Induced CBF Pathway and Cold Tolerance in Watermelon (Citrullus lanatus L.) - Jingjing Chang; Yanliang Guo; Jiayue Li; Zhuangzhuang Su; Chunxia Wang; Ruimin Zhang; Chunhua Wei; Jianxiang Ma; Xian Zhang; Hao Li (MDPI AG, 2021)
Cold stress is a major environmental factor that detrimentally affects plant growth and development. Melatonin has been shown to confer plant tolerance to cold stress through activating the C-REPEAT BINDING FACTOR (CBF) pathway; however, the underlying modes that enable this function remain obscure. In this study, we investigated the role of H2O2 and Ca2+ signaling in the melatonin-induced CBF pathway and cold tolerance in watermelon (Citrullus lanatus L.) through pharmacological, physiological, and genetic approaches. According to the results, melatonin induced H2O2 accumulation, which was associated with the upregulation of respiratory burst oxidase homolog D (ClRBOHD) during the early response to cold stress in watermelon. Besides, melatonin and H2O2 induced the accumulation of cytoplasmic free Ca2+ ([Ca2+]cyt) in response to cold. This was associated with the upregulation of cyclic nucleotide-gated ion channel 2 (ClCNGC2) in watermelon. However, blocking of Ca2+ influx channels abolished melatonin- or H2O2-induced CBF pathway and cold tolerance. Ca2+ also induced ClRBOHD expression and H2O2 accumulation in early response to cold stress in watermelon. Inhibition of H2O2 production in watermelon by RBOH inhibitor or in Arabidopsis by AtRBOHD knockout compromised melatonin-induced [Ca2+]cyt accumulation and melatonin- or Ca2+-induced CBF pathway and cold tolerance. Overall, these findings indicate that melatonin induces RBOHD-dependent H2O2 generation in early response to cold stress. Increased H2O2 promotes [Ca2+]cyt accumulation, which in turn induces H2O2 accumulation via RBOHD, forming a reciprocal positive-regulatory loop that mediates melatonin-induced CBF pathway and subsequent cold tolerance.